Age and Sex Differences in the Association Between Online Gaming Duration and Adolescent Mental Health: A Cross-Sectional Study - Sipahutar, Ida Erni; Suardana, I Ketut; Hartati, Ni Nyoman; Harini, I Gusti Ayu; Gama, I Ketut; Suardani, Ni Luh Ketut; Dewi, Desak Gede Mirah Puspita (Journal of Applied Nursing and Health, 2026)
Background: Online gaming is common among adolescents and may be associated with emotional and behavioural problems. However, evidence from Indonesia remains limited, particularly regarding whether age and sex modify the relationship between gaming duration and adolescent mental health outcomes. To examine whether age and sex moderate the association between online gaming duration and Strengths and Difficulties Questionnaire (SDQ) domains among Indonesian adolescents. Methods: This cross-sectional study followed the STROBE reporting guideline. Participants were students aged 15–18 years who reported playing online games at a public senior high school in Bali, Indonesia (n = 109; total sampling). Online gaming duration (independent variable) was categorized as <1 hour, 1–2 hours, 2–3 hours, 3–4 hours, and >4 hours per day. SDQ domains (dependent variables) included prosocial behavior, hyperactivity/inattention, emotional problems, conduct problems, and peer relationship problems. Moderators were age and sex. Data were analyzed with statistical significance set at p < 0.05. Moderation was tested using a two-way MANOVA with interaction terms. Results: Online gaming duration showed a significant multivariate association with the combined SDQ domains (p < 0.001; partial η² = 0.277). Significant interaction effects were observed for Age × Gaming Duration (p < 0.001; partial η² = 0.433) and Sex × Gaming Duration (p < 0.001; partial η² = 0.376). SDQ total difficulties were classified as abnormal in 81.6% of participants, which was interpreted cautiously as a potential measurement/contextual issue. Conclusion: Gaming duration was associated with adolescent mental health indicators, and the association varied by age and sex. School- and family-based guidance should emphasize balanced digital recreation alongside sleep, study, and offline social activities, with screening and referral pathways for adolescents reporting emotional or behavioral difficulties